2022
DOI: 10.3390/polym14040785
|View full text |Cite
|
Sign up to set email alerts
|

Chitin-Glucan Complex Hydrogels: Optimization of Gel Formation and Demonstration of Drug Loading and Release Ability

Abstract: Chitin-glucan complex (CGC) hydrogels were fabricated through a freeze–thaw procedure for biopolymer dissolution in NaOH 5 mol/L, followed by a dialysis step to promote gelation. Compared to a previously reported methodology that included four freeze–thaw cycles, reducing the number of cycles to one had no significant impact on the hydrogels’ formation, as well as reducing the total freezing time from 48 to 18 h. The optimized CGC hydrogels exhibited a high and nearly spontaneous swelling ratio (2528 ± 68%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 55 publications
(86 reference statements)
4
17
0
Order By: Relevance
“…The CGC hydrogels were prepared as described by Araújo et al [ 24 ], with slight modifications. Briefly, the CGC powder was dispersed in a NaOH 5 mol/L solution, at two biopolymer concentrations (4 and 6 wt%), and the suspensions were kept at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CGC hydrogels were prepared as described by Araújo et al [ 24 ], with slight modifications. Briefly, the CGC powder was dispersed in a NaOH 5 mol/L solution, at two biopolymer concentrations (4 and 6 wt%), and the suspensions were kept at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…CGC hydrogels can be fabricated by polymer coagulation from an alkali solution [ 23 ]. The procedure involves CGC dissolution in alkali solvent systems based on NaOH [ 24 ], to which freeze-thaw cycles are applied. CGC-based physical hydrogels spontaneously form during dialysis of the CGC alkali solution in water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delivery system behavior appeared different in relation to the kind of solution in which it was. Indeed, the release rate followed Fick’s diffusion when hydrogel was immersed in a PBS solution and a non-Fickian diffusion in a NaOH 0.9% solution [ 137 ].…”
Section: Controlled Release Systems For Caffeinementioning
confidence: 99%
“…Meanwhile, it was found that drug release time of chitosan-polyvinyl alcohol hydrogel loaded with drug was up to 30 h ( 61 ). Recently, the characteristics of high water absorption, swelling, mechanical and rheological properties were also observed in chitin-glucan complex hydrogels fabricated by freezing and thawing ( 64 ).…”
Section: Preparation Of Hydrogelsmentioning
confidence: 99%